Support for the replicability of imagined contact effects - Crisp, Richard John; Miles, Eleanor; Hüsnü, Shenel (Hogrefe Verlag GmbH & Co. KG customerservice@hogrefe-publishing.com, 2014)
As part of their Many Labs project Klein et al. (2014) replicated the effects of an imagined contact study carried out by Husnu and Crisp (2010). In their report the authors argue the data provides weak support for replicability. However, the effect observed was both significant and comparable to that obtained from a recent meta-analysis for the relevant outgroup. This suggests that the Many Labs project may provide stronger support for the existence of imagined contact effects than currently thought. We discuss the value in interpreting replications within the context of the existing literature. © 2014 Hogrefe Publishing.
Keywords: Imagery; Imagined contact; Interventions; Prejudice